2023
DOI: 10.1155/2023/6671523
|View full text |Cite
|
Sign up to set email alerts
|

Dual Solutions and Stability Analysis of Cu-H2O-Casson Nanofluid Convection past a Heated Stretching/Shrinking Slippery Sheet in a Porous Medium

Kifle Adula Duguma,
Oluwole Daniel Makinde,
Lemi Guta Enyadene

Abstract: In this study, we examined the impact of Cu-H2O nanoparticles on two-dimensional Casson nanofluid flows past permeable stretching/shrinking sheet embedded in a Darcy-Forchheimer porous medium in the presence of slipperiness of surface, suction/injection, viscous dissipation, and convective heating. Using some realistic assumptions and appropriate similarity transformations, the governing nonlinear partial differential equations were formulated and transformed into a system of nonlinear ordinary differential eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 40 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The result indicated that flow of fluid with higher magnetic flux can be enhanced in slip regime". "Dual solution and stability analysis of Cu-H2O-Casson nanofluid convection past a heated stretching/shrinking slippery sheet in a porous medium, was examined" by Duguma et al [41]. Motivated by the above cited literature, the aim is to carefully study the characteristics flow pattern of hybrid nanofluid slip flow over a permeable sheet with radiative heat flux, variable thermal conductivity and heat source.…”
mentioning
confidence: 99%
“…The result indicated that flow of fluid with higher magnetic flux can be enhanced in slip regime". "Dual solution and stability analysis of Cu-H2O-Casson nanofluid convection past a heated stretching/shrinking slippery sheet in a porous medium, was examined" by Duguma et al [41]. Motivated by the above cited literature, the aim is to carefully study the characteristics flow pattern of hybrid nanofluid slip flow over a permeable sheet with radiative heat flux, variable thermal conductivity and heat source.…”
mentioning
confidence: 99%